New Dn+1(2) K-matrices with quantum group symmetry. (30th August 2018) - Nepomechie, Rafael I; Pimenta, Rodrigo A
Abstract: We propose new families of solutions of the boundary Yang–Baxter equation. The open spin-chain transfer matrices constructed with these K-matrices have quantum group symmetry corresponding to removing one node from the Dynkin diagram, namely, , where . These transfer matrices also have a duality symmetry. These symmetries help to account for the degeneracies in the spectrum of the transfer matrix.